Tour operation system - Chee, Yeh Yun (Universiti Malaysia Sarawak (UNIMAS), 2015)
Resource management is a systematic way of organizing resources. A system proposed for the management of resources is therefore essential to ensure each of the allocation of resources can be maximized to fulfill the organization's demand in an effective and efficient way, leverage time saving and performance in an organization. Tour Operation System is a resources managing and scheduling system that is designed based on the requirement obtained from the tour operation department of a tour agency named Sabah Tour & Travel Agency. This system is built to overcome the problem of their working environment whereby paper-based in organizing and managing resources and work shift is still be used, causing inconsistency and lack of systematic in their management. By using the system, timesheet will be created for the employees, allowing them to be notify about their working schedule days ahead instead of getting last minute information like how they faced now. A few more features and functions that will be included in the system design are determined after studies have been made on the similar system on the market, such as mobility features and feedback channel. The system will create a value for the tour agency by promoting efficiency in collaboration and employee working schedule management.